The fragile boundary between ‘education’ and ‘educationalisation’: some personal reflections on the often exaggerated educational aspirations of museums - Depaepe, Marc (Historia y Memoria de la Educación, 2021)
Although the origins of school museums and museums of children and childhood do not coincide directly, they nevertheless have moved into the same direction during the past decades. Especially because children are an important part of the visitors, a lot is invested by these museums in educational support and activities. Pedagogical arguments form the backbone of their mission statements. A bit against the tide of this trend, I want to pay attention here to the often exaggerated educational aspirations. To my mind the boundary between “education” and “educationalisation” is a fragile one and can be easily exceeded if the cultural-historical context of the museum content is ignored too much. Educating young people does not necessarily mean taking them by the hand and leading them through well-developed work packages, but is related to the more complex process of Bildung – the formation of a person, which usually starts, in view of attitudes and behaviour, by reflection about self-identity as well as societal values and norms. In my opinion the encounter with well-chosen artefacts of former pedagogical mentalities and realities in museums of education, children and childhood, can be helpful in this respect. Therefore, my plea for more culture-historical contemplation and less educational strategy in representing education, children and childhood is not to be understood as phasing efforts in this sector. On the contrary, the shift of emphasis from the neoliberal focus on efficiency, management, and social relevance (also in terms of a possible instrumentalization) of educational history towards more scientific, cultural-historical underpinning will need continuous support.